Do the benefits of learning to write a compare-contrast text transfer to other types of writing task? Analysing the effects of strategy-focused instruction - Rodríguez-Málaga, Lucía; Rodríguez, Celestino; González-Sánchez, Lorena; Areces, Débora; Cueli, Marisol (Anales de Psicología / Annals of Psychology, 2024)
Cognitive Self-Regulation Instruction (CSRI) program is a strategy-focused instruction with three instructional components for improving students’ writing product (direct teaching, modelling, and peer-practice). The present study aimed to explore whether the CSRI program leads to spontaneous transfer, improving the writing product (in terms of quality, structure, and text coherence) of an uninstructed genre (opinion text); and to examine whether the order in which the instructional components were implemented had an effect. A total of 126 students in their 4thyear of primary school participated in the study. They were randomly assigned to one of two experimental conditions which received the CSRI but differed in the order the instructional components were delivered, or to a control condition which followed the traditional teaching approach. Our findings show that both CSRI sequences produced benefits in terms of greater structure and coherence of the writing product in the opinion text at post-test but not 8months after the intervention. In consequence, for students to be able to adequately transfer strategies to uninstructed text genres, they need teachers to teach them how to do it effectively.